Assessment of biofilm formation in Pseudomonas aeruginosa by antisense mazE-PNA. (March 2017) - Valadbeigi, Hassan; Sadeghifard, Nourkhoda; Salehi, Majid Baseri
Abstract: The hallmark patogenicity in Pseudomonas aeruginosa (P. aeruginosa) is biofilm formation that is not easy to eradicate, because it has variety mechanisms for antibiotic resistance. In addition, toxin-antitoxin (TA) system may play role in biofilm formation. The current study aimed to evaluate the role of TA loci in biofilm formation. Therefore, 18  P. aeruginosa clinical isolates were collected and evaluated for specific biofilm and TA genes. The analysis by RT-qPCR demonstrated that expression of mazE antitoxin in biofilm formation was increase. On the other hand, mazE antitoxin TA system was used as target for antisense PNA. mazE -PNA was able to influence in biofilm formation and was inhibit at 5, 10 and 15 μM concentrations biofilm formation in P. aeruginosa. Therefore, it could be highlighted target for anti-biofilm target to eradicate P. aeruginosa biofilm producer. Highlights: Our finding demonstrated that different biofilm observed in various clinical isolates. mazE (antitoxin) showed regulator of biofilm production. mazE introduce as a potent target for eradication of biofilm formation.